Oral signs and symptoms and hyperglycemic status of type II diabetic patients in relation to cytomorphometric findings of gingival and buccal cytobrush smears - Baban, Mohammad T; Garib, Balkees T (Journal of Baghdad College of Dentistry, 2013)
Background: Brush cytology is an accepted technique that gets renewed interest. It is now used as an aid for the diagnosis and observation of possible epithelial changes that could be associated with oral mucosal diseases. This study aimed to evaluate the cytomorphometric changes in gingiva and buccal mucosa of type II diabetics and to assess their relation to oral symptoms and glycemic status. Materials and methods: Cytological Papanicolaou stained smear were prepared from cheek and gingiva of 20 non treated cases, 20 treated diabetics and 20 healthy persons of both sex after measuring their HbA1c and recording their oral symptoms. Hundred unfolded epithelial cells were evaluated qualitatively using MCID software to measure nuclear and cytoplasmic areas, ratio, perimeters, and form factors. Different statistical analyses were used to determine relations between studied parameters. Results: Diabetics smears showed large nucleus, small cytoplasm, and small cytoplasm/nucleus ratio compared with healthy persons with no sex variation. Xerostomia and burning sensation were significantly correlated with nuclear parameters, while HbA1c was significantly correlated with both cytoplasmic and nuclear parameters. Well-controlled patients showed reduction in nuclear area, but nucleus and cytoplasm form factors were unlike normal. Conclusions: Oral cytology from type II diabetics is associated with detectable cytomorphometric changes that is better demonstrated in buccal than gingival mucosa and tend to return partially to their normal values in well-controlled patients, with no sex variation. NA seems to be the main parameter that changed during hyperglycemia and xerostomia, while both NA and CA were related to burning sensation.